Divorce settlement or leaving the club? A breakdown of the Brexit bill - Zsolt Darvas; Konstantinos Efstathiou; Inês Goncalves Raposo (Bruegel, 2017)
The `Brexit bill' is an expected payment to be made by the United Kingdom that would settle its financial commitments when it leaves the European Union. While authors of this Working Paper consider the financial settlement the least important economic issue in the Brexit negotiations, a conditional agreement at least on the methodology for calculating the Brexit bill could be a prerequisite for the more meaningful discussions on the new EU-UK economic relationship after Brexit, such as future trade, financial services and labour mobility cooperation. To bring transparency to the debate and to foster a quick agreement on the bill, the authors make a comprehensive attempt to quantify the various assets and liabilities that might be factors in the financial settlement. The size of the Brexit bill will depend on fundamental political compromises and choices, which is discussed. Based on the different scenarios, the long-run net Brexit bill could range from exteuro25.4 billion to exteuro65.1 billion, possibly with a large upfront UK payment followed by significant EU reimbursements later.
Keywords: 330